Preliminaries - Blanco-Mesa, Fabio (Unidad Editorial UPTC, 2020)
CopyrightRevista Inquietud Empresarial© School of Business Administration, Faculty of Economic and Administrative Sciences, Universidad Pedagógica y Tecnológica de Colombia. The publication rights of the articles that appear in each edition belong to the Escuela de Administración de Empresas of the Universidad Pedagógica y Tecnológica de Colombia. The reproduction and citation of the material contained in the journal is authorized, as long as it is explicitly indicated: name of the journal, name of the author(s), year, volume, number and pages of the source article. The mention of commercial products or firms in the journal does not imply a recommendation or endorsement by the University or the School; the use of such products should follow the recommendations on the labels. Translated with www.DeepL.com/Translator (free version)